Development and Validation of a clinical scale for defining RBD severity in participants of the North American Prodromal Synucleinopathy (NAPS) consortium. (20th December 2022) - Choudhury, Parichita; Busicescu, Andrea; Lee‐Iannotti, Joyce; Rangan, Pooja; Shprecher, David; Ju, Yo‐El; Boeve, Bradley F.; Postuma, Ronald B; ,
Abstract: Background: REM Sleep Behavior Disorder (RBD) is a prodromal marker of α‐synucleinopathies with no standardized tool for assessing severity in clinical or research practice. RBD severity may have implications in measuring risk of phenoconversion, monitoring response to treatment and clinical trial design. This study assessed the validity of the RBD symptom severity scale (RBDSSS) and its correlation to the clinical global impression of severity (CGI‐S) in a cohort of participants enrolled in the North American Prodromal Synucleinopathy (NAPS) Consortium. Method: Participants and their bedpartners enrolled in the NAPS cohort filled out an 8‐item questionnaire, developed by the International RBD Study Group, assessing frequency and severity of dreams, vocalizations, movements, and injuries associated with RBD, with higher scores indicating more severe symptoms. The CGI‐S is a 7‐point scale ranging from normal (1) to most severely ill (7) and was completed by a clinician based on an independent interview with the participant ± their bedpartners. Total scores for participant (RBDSSS‐PT) and bed partner (RBDSSS‐BP) questionnaires were derived by multiplying frequency and severity scores for each feature, then summing the products for possible maximum scores of 54 and 38 respectively. Result: This cohort (n = 212) was predominantly male (82.5%) with a mean ± SE age of 65.16 ± 1.46 years. The median (interquartile range) for RBDSSS‐PT, RBDSSS‐BP and CGI‐S was 11 (4‐17), 8 (4‐14.3) and 3 (3‐4), respectively. Spearman's rank correlation coefficients (rs ) were as follows: RBDSSS‐PT vs. RBDSSS‐BP, rs = 0.579; RBDSSS‐PT vs. CGI‐S, rs = 0.642; RBDSSS‐BP vs. CGI‐S, rs = 0.487 (all P <0.0001). RBDSSS‐BP scores were significantly lower in women (6 vs. 9, Chi‐Square p = 0.009) while there were no differences in RBDSSS‐PT scores by sex. (9 vs. 11, p = 0.473). Conclusion: A moderate correlation was observed between RBDSSS‐PT and RBDSSS‐BP suggesting good construct validity for the scale. CGI‐S correlated most with RBDSSS‐PT and had a weaker association with RBDSSS‐BP. Women had lower severity scores as reported by bed partners unlike their self‐reported scores, indicating possible sex differences in perceived RBD severity.